Vegetation suppression offset in the Environmental Licensing of Small Hydroelectric Power Plants in Minas Gerais – Brazil (Research, Society and Development, 2022)
The exploitation of environmental resources by humanity has always existed, with the vegetation suppression being one of the most recurrent. Social mobilization for the environmental issue gave rise to the environmental offset mechanism, which aims to balance the negative impacts of a project that could not be avoided or mitigated. The offset proposal must comply with three principles: proportionality (relationship between damage caused and compensation), spatial connection (it must be close to or in the same watershed as the impacted area) and functional connection (it must promote the replacement of lost ecological functions). This work evaluates how the environmental offset of vegetation suppression is presented in the Environmental Impact Statements of Small Hydroelectric Power Plants in Minas Gerais State, Brazil. All six cases identified between 2018 and 2021 in the licensing system were analyzed. Data were analyzed using documentary research and content analysis of the studies, applying three criteria based on the principles of offset, evaluated as "met", “partially met” and “not met”. The results indicate that only two studies fully met the adopted criteria, and the functional connection and proportionality presented, respectively, the best and worst results. This panorama reveals the lack of detail in the information presented in the studies and the need for improvement. An alarming result is that in four of the five applicable cases, the Atlantic Forest Law was not fully complied with. It is expected that this study can contribute to the improvement of the mechanism, as well as assist in Brazilian environmental legislation.